1992
DOI: 10.1073/pnas.89.17.7866
|View full text |Cite
|
Sign up to set email alerts
|

Mutational spectrum at the Hprt locus in splenic T cells of B6C3F1 mice exposed to N-ethyl-N-nitrosourea.

Abstract: We have determined the mutational spectrum of N-ethyl-N-nitrosourea (ENU) in exon 3 of the hypoxanthine guanine) phosphoribosyltransferase gene (Hprt) in splenic T cells following in vivo exposure of male B6C3F1 mice (5-7 weeks old) to ENU. Hpir mutants were isolated by culturing splenic T cells in microtiter dishes containing medium supplemented with interleukin 2, concanavalin A, and 6-thiouanine. DNA was extracted from 6-thoa ne-sistant colonies and amplified by the polymerase chain reaction (PCR) using pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
51
1

Year Published

1994
1994
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(63 citation statements)
references
References 33 publications
11
51
1
Order By: Relevance
“…The proportion of frameshifts coincides most closely with 27% observed in Big Blue Rat2 cell lines (20), compared with 11% in mice (24). The percentage of frameshift mutations decreased in the ENU-exposed fish, which is also consistent with studies showing ENU does not induce high numbers of frameshift mutations (31,44).…”
Section: ϫ5supporting
confidence: 77%
“…The proportion of frameshifts coincides most closely with 27% observed in Big Blue Rat2 cell lines (20), compared with 11% in mice (24). The percentage of frameshift mutations decreased in the ENU-exposed fish, which is also consistent with studies showing ENU does not induce high numbers of frameshift mutations (31,44).…”
Section: ϫ5supporting
confidence: 77%
“…In addition, the ENU-induced adducts 04-ethylthymine and 02-ethylthymine induce ART --GC transitions (34) and ART -* T-A transversions (35), respectively. Slow repair of 02-and 04-ethylthymine adducts has been suggested to contribute to increases in observed mutations at A-T base pairs over time (36,37) and, therefore, should be detected at 90 days, as seen in our studies ( Table 2). This result suggests that the observed spectra result from adduct-specific repair rates and the mutagenic potential of the ENU-induced adducts.…”
Section: Discussionsupporting
confidence: 57%
“…They occur predominantly in A-T base pairs (70%), indicating that this lacZ surrogate mutation model detects a high proportion of ENU-induced mutations similar to, but at a somewhat lower frequency than, those observed in some endogenous mammalian genes-for example, offspring in the specific locus test [86% (28)] and in the somatic hprt mutations in the mouse Genetics: Douglas et al [90% (29)] and monkey [94% (30)], although any differences may simply be the result of different experimental conditions including dose (31). The proportion of mutations in AT vs. G-C base pairs in the present study is nearly identical to that reported for the lacI transgenic model [i.e., 68% (5)].…”
Section: Discussionmentioning
confidence: 99%